High fucoxanthin wakame (Undaria pinnatifida) prevents tumor microenvironment formation in an AOM/DSS mouse carcinogenic model. (January 2020) - Terasaki, Masaru; Kuramitsu, Yasuhiro; Kojoma, Mareshige; Kim, Sang-Yong; Tanaka, Takuji; Maeda, Hayato; Miyashita, Kazuo; Kawagoe, Chikara; Kohno, Shoui; Mutoh, Michihiro
Graphical abstract: Highlights: More than 5.0 mg fucoxanthin per g dry weight (Fx-high) of wakame could be cultivated. Fucoxanthin-high wakame itself has a cancer chemopreventive potential but not a pure fucoxanthin. Fucoxanthin-high wakame prevent tumor microenvironment formation in colon carcinogenic mice. Salivary glycine is a predictor correlated with the chemopreventive efficacy of Fx-high wakame. Abstract: Fucoxanthin (Fx) is a major xanthophyll in Undaria pinnatifida (wakame) and is one of the potent carotenoids against cancer development. However, the cancer preventive function of high fucoxanthin (Fx-high) wakame itself has not been well investigated. Therefore, we cultivated Fx-high wakame and investigated the effect of this alga on a AOM/DSS carcinogenesis mouse model. Fx-high wakame (Fx 30 mg/kg body weight) significantly decreased the number of cells that compose the tumor microenvironment compared to mice without wakame. The number of colorectal cancer stem cell-like CD44 high /EpCAM high cells, cancer-associated fibroblast-like αSMA high cells, tumor-associated macrophage-like and dendritic cell-like CD206 high cells were significantly decreased 0.6-, 0.5-, and 0.5-fold, respectively, and apoptotic cell-like cleaved caspase-3 high cells were significantly increased 1.7-fold by Fx-high wakame. Moreover, salivary glycine was decreased 0.4-fold by Fx-high wakame. Our results imply that Fx-high wakame could prevent formation of the tumor microenvironment with a salivary predictor of the Fx-high wakame function.